2016
DOI: 10.1016/j.appet.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Make up your mind about food: A healthy mindset attenuates attention for high-calorie food in restrained eaters

Abstract: Attention bias for food could be a cognitive pathway to overeating in obesity and restrained eating. Yet, empirical evidence for individual differences (e.g., in restrained eating and body mass index) in attention bias for food is mixed. We tested experimentally if temporarily induced health versus palatability mindsets influenced attention bias for food, and whether restrained eating moderated this relation. After manipulating mindset (health vs. palatability) experimentally, food-related attention bias was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
62
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 39 publications
(53 reference statements)
11
62
7
Order By: Relevance
“…reaching for a tempting food ( Anderson, 2017 ; Krebs et al, 2010 ). Another possibility is that selective attention to sensory/hedonic attributes of food biases choice towards food consumption because these attributes of food are weighed more strongly than longer-term goals in reward valuation processes ( Werthmann et al, 2016 ).…”
Section: Cognitive Processes Involved In Responses To Food Cues Beformentioning
confidence: 99%
“…reaching for a tempting food ( Anderson, 2017 ; Krebs et al, 2010 ). Another possibility is that selective attention to sensory/hedonic attributes of food biases choice towards food consumption because these attributes of food are weighed more strongly than longer-term goals in reward valuation processes ( Werthmann et al, 2016 ).…”
Section: Cognitive Processes Involved In Responses To Food Cues Beformentioning
confidence: 99%
“…Furthermore, glucose intake enhanced attentional food bias in obesity [41] and intra-individual variability in a similar bias measure was stronger in obesity [64], supporting the dynamic nature of attentional bias [164•]. Food attentional bias can be attenuated by cognitive factors such as a healthy mindset [87], which emphasises the importance of cross-talk between the frontostriatal loops. Regulation of craving has been associated with differential activation in the putamen and functional connectivity between the putamen and dlPFC [50], also spanning the loops.…”
Section: Food-related Attentional Bias and Cravingmentioning
confidence: 92%
“…These studies have shown that both restrained [16] and external eaters (individuals who eat in response to external food cues) [11,18,19] respond faster to a range of hypercaloric food stimuli relative to neutral (non-food) stimuli. On the other hand, of relevance for the present study, research on attention processes in participants with overweight and obesity is relatively sparse, and it yielded contradictory results [20].…”
Section: Introductionmentioning
confidence: 80%